Analisa dimensi pori sponge sebagai pelat penyerap terhadap kinerja solar still double slope tipe v - Habib Indradaya; Nova R. Ismail; Akhmad Farid (Universitas Muhammadiyah Metro, 2020)
There have been many studies for the development of solar distillation to increase its efficiency and economic benefit, component design improvement of the solar still is one of the directions to increase its productivity. To facilitate desalinate-water evaporation a thin stream. Thin stream water flow is needed, which can be obtained by flowing feed water through the pores in a capillary manner. Therefore, research on the effect of sponge pore dimensions on the performance of solar still double slope type V is performed. This research was carried out experimentally to compare the pore dimensions of sponges with the performance of solar still double slope type V. The results of this study indicate that the best solar still double slope type V is using 0.089 mm sponge dimensions, with an obtained capillary flow rate of sponge at 0.0000043 m/s in average efficiency of 37.311 %, and the yield of condensate water per day is 3,447 liters/m2.Keywords: Pore dimension, sponge absorbent plate, solar still.